Effect of cup lump rubber as a sustainable bio-modifier on the properties of bitumen incorporating polyphosphoric acid - Ansari, Anwaar Hazoor; Mohd Jakarni, Fauzan; Muniandy, Ratnasamy; Hassim, Salihudin; Elahi, Zafreen; Zair, Mohamed Meftah Ben (Elsevier, 2022)
The growing demand for non-renewable resources is a significant problem these days, and one such resource is bitumen, which is a prime component of flexible pavement. Thus, researchers are striving to find novel approaches such as bitumen bio-modifiers to extend the service life of pavements. One such bio-modifier is the natural cup lump rubber (CLR). This study aims to investigate the physical, rheological, storage stability, morphological and chemical properties of the CLR and CLR-polyphosphoric acid (PPA) modified bitumen. In this study CLR (3%, 6%, 9% and 12%) was used to modify the bitumen and 0.5 wt% PPA was proposed as a co-modifier to alleviate the instability and phase separation at higher temperatures. The CLR was pre-treated with xylene prior to blending with the bitumen. The penetration has systematically decreased while the softening and rotational viscosity increase with increasing CLR content. Moreover, the addition of the PPA further enhanced the rheological properties and provided a better viscoelastic response at higher temperatures. Also, the CLR and PPA combination potentially enhanced the pavement resistance to rutting and fatigue damage. Furthermore, the inconsistencies in storage stability for CLR modified bitumen at 9% and 12% have improved by incorporating the PPA. The field emission scanning electron microscope (FESEM) analysis indicated that the CLR particles at higher content are dispersed in the base bitumen with a small agglomeration and a clear interface. In contrast, the addition of PPA improved the dispersion and mitigated the agglomeration. In conclusion, the CLR with 0.5 wt% PPA is applicable to produce the hybrid modified bitumen with enhanced performance compared to base, and only CLR modified bitumen. However, the bitumen containing 3% and 6% CLR with 0.5 wt% PPA, and the modified bitumen with 9% CLR have shown promising performance.